A global phenomenon the case of Aldub - Misme, Modjelen; Villalobos, May Lynn. (2016.)
This qualitative study describes a global phenomenon, traces the beginnings of the AlDub loveteam, identifies the factors that made AlDub a national and global phenomenon, discusses the convergence between GMA network and AlDub, and gives implications on AlDub as a global phenomenon. It is supported by Kincaid and Rogers? Convergence Theory which defines communication as the process where participants share and create information, and must have a common interest in order to reach a mutual understanding. Data were gathered through Key Informant Interviews and online research (for Kantar/TNS audience share and official list of advertisements). Results show that what made AlDub a global phenomenon is its new and extraordinary segment Kalyeserye and its Big Fan Base which comprises of the AlDub-MaiDen Nation who are the lead information propagators on and off cyberspace, unaffiliated fans who are the charity funders and the OFWs who are the word-of-mouth propagators outside the country. The findings also showed that AlDub?s future is uncertain but they should transition to other formats for them to thrive as artists.
Thesis -- Bachelor of Arts in Communication and Media Studies. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Aldub; Global phenomenon; Kelyeserye